Flavones as natural photoinitiators for light mediated free‐radical polymerization via light emitting diodes. Issue 2 (20th January 2020) - Al Mousawi, Assi; Garra, Patxi; Dumur, Frédéric; Graff, Bernadette; Fouassier, Jean Pierre; Lalevée, Jacques
ABSTRACT: In this work, we propose the use of flavones that can be derived from natural products as versatile high performance visible light photoinitiators initially with amino acid and later with iodonium salt and phosphino benzoic acid combinations for free‐radical polymerization acrylates of thin specimen (25 μm) and methacrylates thick specimen (1.4 mm) upon illumination with near ultraviolet light or visible light utilizing light emitting diodes (LED)@385 nm and LED@405 nm. High polymerization initiating capabilities are found with different hydroxyflavones and high final conversions of the reactive function are obtained. Their application as materials for three‐dimensional (3D) printing patterns is especially carried out for 1 mm thick 3D printed photopolymers. A full description of the comprised photochemical mechanisms is additionally given. © 2020 Wiley Periodicals, Inc. J. Polym. Sci. 2020, 58, 254–262 Abstract : Flavones derived from natural products are presented here as versatile high performance visible light photoinitiators combined with amino acid or iodonium salt for free‐radical polymerization of (meth)acrylates. Examples in composites or three‐dimensional printing are provided.